Correction: Diagnostic and therapeutic aspects of recurrent renal stone disease - Meyers, Anthony; Whalley, Natalie; Martins, Maria (African Journal of Nephrology, 2017)
In Table 3 of the original publication of this article [1], the citrate excretion in white subjects is given as 1.39(0.92), which is incorrect. The correct value is 2.39(0.92). Reference 1. Meyers A, Whalley N, Martins M. Diagnostic and therapeutic aspects of recurrent renal stone disease. Afr J Nephrol. 1998; 2(1):12-17.